SPIRIT TRADISI LOKAL PADA ERA GLOBAL: STUDI DESA WISATA PENGELIPURAN BANGLI BALI - Raka I Nyoman (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2018)
The central issue of this research is the spirit of the local tradition of the tourism village in the global era. This issue is interesting because, dismissing the views of optimistic globalists who view, global culture suppresses local culture. This view is not proven, because the local tradition of Pengelipuran village is still effective in attracting local, national and global tourists. Why are global tourists interested in local traditions? How did this happen? The three research questions are: 1) What is the tradition of Pengelipuran Tourism Village? 2) Why does this tradition attract the attention of local, national and global tourists? 3) What is the Spirit of the Tourism Village in the Global Era? There are three theories that are explored to manggali, and analyze research data, namely: 1) Existence Theory, seeing the essence and existence of Penglipuran tourism village; 2) Globalization Theory, to see the village tradition of tourism from three perspectives: the globalists, the traditionalists and the transpormationalists. 3) Deconstruction theory, to see the text and context of the tradition of the village tourism in the era of globalization. Data were analyzed through four interpretive descriptive analysis. Searching data with the three theories above found the satya attitude of the penguripuran community in terms of: 1) maintaining the village tradition of Pengelipuran in the form of: a) consistency in the form of houses, angkulangkul, using local products (bamboo), b) coral tradition blending, maintaining the system monogamy. c) tradition of keeping clean air, pollutionfree village air, d) consistency of attitude and application of village concepts when patra.2) consistency of the attitude of togetherness of the community in maintaining a unique tradition, becoming the capital of tourism village development. 3) the similarity of attitudes and views in maintaining the uniqueness of tradition is the spirit of the local village in the global era. The conclusions, satya semaya, satya discourse, and satya laksana in maintaining the spirit of togetherness, and consistency in maintaining tradition become the spirit of the village of tourism. Keywords: Globalization, Spirit, Tourism Village